2022
DOI: 10.1088/1755-1315/1081/1/012017
|View full text |Cite
|
Sign up to set email alerts
|

Form Factor Prediction Based on Ship Model Test Data by Statistical Method

Abstract: The ship model resistance test is carried out on the towing tank with a certain scale to get the total resistance coefficient of the ship model. The value of the ship’s form factor is needed in extrapolation calculations to get the coefficient and total resistance value of a full-scale ship. The form factor can be obtained using the traditional method, namely testing the resistance of the ship model with a Froude Number between 0.1 – 0.2. This method is known as the Prohaska method. Another method or a more mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This study uses the least squares multiple linear regression method to determine the Form Factor, which will be compared with the Prohaska method. The principle dimensions of ship displacement (LWL, B, T, CB, CM, CP, and WSA, ) will be the predictor variables, where the previous research conducted by Widodo et al (2022) found outlier data [21].…”
Section: Form Factormentioning
confidence: 99%
“…This study uses the least squares multiple linear regression method to determine the Form Factor, which will be compared with the Prohaska method. The principle dimensions of ship displacement (LWL, B, T, CB, CM, CP, and WSA, ) will be the predictor variables, where the previous research conducted by Widodo et al (2022) found outlier data [21].…”
Section: Form Factormentioning
confidence: 99%
“…-While the coefficient of frictional resistance (CF) is obtained from the calculation with the equation: -Prediction of form factors (1+k) [43,44], obtained using the Prohaska method [45,46]. -The coefficient of total vessel resistance (CT) and Correlation Allowance (CA) [24] is the additional coefficient to the ship model's correlation resistance.…”
Section: Determination Of the Ship's Resistancementioning
confidence: 99%